Synthesis and characterization of hydrogels based on poly(2-hydroxyethyl methacrylate) for drug delivery under UV irradiation - Senol, Sebnem; Akyol, Emel (SPRINGER, 2018)
The present study aims to create a controlled release system through the preparation and characterization of hydrogels based on 2-hydroxyl ethyl methacrylate (HEMA). In order to investigate the influence of photo-initiators on the drug release behavior of the resulting hydrogels, three different photo-initiators [2,2-dimethoxy-2-phenyl-acetophenone] (Irgacure 651), 1-hydroxycyclohexyl phenyl ketone (Irgacure 184) and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959) were used. In addition, hydroxyapatite (HAp) was employed to modify HEMA hydrogels. The synthesis of hydrogels was confirmed by characterization through Fourier transform infrared spectroscopy, nuclear magnetic resonance (C-13 NMR) spectroscopy and digital microscope. The responsive behaviors were investigated by recording swelling ratios under different conditions. In vitro drug release studies were performed for donepezil hydrochloride-loaded hydrogels at pH 1.2, 6.8 and 7.4. The results indicated that hydrogels synthesized using Irgacure 2959 released the maximum amount of donepezil hydrochloride. Moreover, the release rate decreased in the presence of HAp.
Keywords: CONTROLLED-RELEASE; IN-VITRO; ENGINEERING APPLICATIONS; POLY(ETHYLENE GLYCOL); HYDROXYAPATITE; DONEPEZIL; SYSTEMS; NANOPARTICLES; COMPOSITES; PHOTOPOLYMERIZATION; Materials Science